2021
DOI: 10.1021/acs.nanolett.1c03214
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Platform for Fast Low-Voltage Nanoelectromechanical Switching

Abstract: The use of molecules as active components to build nanometer-scale devices inspires emerging device concepts that employ the intrinsic functionality of molecules to address longstanding challenges facing nanoelectronics. Using molecules as controllable-length nanosprings, here we report the design and operation of a nanoelectromechanical (NEM) switch which overcomes the typical challenges of high actuation voltages and slow switching speeds for previous NEM technologies. Our NEM switches are hierarchically ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Using molecules as length-controllable nano springs, Han et al, reported the design and operation of a nanoelectromechanical switch that overcomes the typical challenges of high actuation voltages and slow switching speeds. [303] The molecular distance between the upper and lower electrodes can be efficiently changed by electrostatic mechanical force by applying different biases and substituting molecular systems with varying chain lengths. This allows the switching between high and low conductivity states.…”
Section: Applications Of Single-molecule/atom Conductance Switchesmentioning
confidence: 99%
“…Using molecules as length-controllable nano springs, Han et al, reported the design and operation of a nanoelectromechanical switch that overcomes the typical challenges of high actuation voltages and slow switching speeds. [303] The molecular distance between the upper and lower electrodes can be efficiently changed by electrostatic mechanical force by applying different biases and substituting molecular systems with varying chain lengths. This allows the switching between high and low conductivity states.…”
Section: Applications Of Single-molecule/atom Conductance Switchesmentioning
confidence: 99%
“…The continuous miniaturization of CMOS field-effect transistors (FETs) faces challenges related to off-state current leakage and power dissipation . NEM switches have attracted attention in recent years due to their merits of near zero off-state current, steep subthreshold slopes, and robustness in extreme environments. Han et al fabricated NEM switches using DEP assembled gold nanorods as active components (Figure a). Single gold nanorods were bridged between a pair of gold electrodes with self-assembled molecular spacers between the nanorod and electrodes.…”
Section: Optical Field-directed Assemblymentioning
confidence: 99%
“…(a) Fabrication of NEM switches using DEP assembled gold nanorods as active components. Reprinted with permission from ref ( 448 ). Copyright 2021, American Chemical Society.…”
Section: Optical Field-directed Assemblymentioning
confidence: 99%
“…An important bottleneck in molecular electronics applications is their considered limited speed capabilities when compared to standard semiconductor device technologies. Even though a few reports of fast switching molecular devices can be found in the literature 14,15 , their integration into scalable circuitry remains elusive. The switching of SCO materials can occur at the ns time scale when their size is reduced down to the nanoscale, at which one can still take advantage of the molecules collective behavior.…”
mentioning
confidence: 99%